The Effect Of Entrepreneurship Training And Entrepreneurship Education On Entrepreneurial Motivation With Entrepreneurial Intention As A Mediating Variable (Case Study of High School Students in Mojokerto City) - Nuryanti, Rizky; Nurika Restuningdiah; Ludi Wishnu Wardana (International Journal of Technology and Education Research, 2025)
This study aims to analyze the direct influence of Entrepreneurship Training and Entrepreneurship Education on Entrepreneurial Motivation, and to examine the mediating role of Entrepreneurial Intention in this relationship among high school students in Mojokerto City. The research employed a quantitative approach with a causal associative design. Data were collected from 344 student respondents and analyzed using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method. The findings indicate that both Education and Training have a strong, positive, and significant influence on both Entrepreneurial Motivation and Entrepreneurial Intention. Entrepreneurial Intention was also found to positively and significantly influence Entrepreneurial Motivation. However, a key finding revealed a paradoxical mediation path: Entrepreneurial Intention negatively and significantly mediates the influence of Entrepreneurship Training (Indirect Coefficient: -0.196; p-value: 0.001) and Entrepreneurship Education (Indirect Coefficient: -0.189; p-value: 0.001) on Entrepreneurial Motivation. The study concludes that although education and training are effective in fostering strong intention, this intention does not always successfully translate into sustained entrepreneurial motivation. Strengthening the entrepreneurship ecosystem outside the classroom, such as continuous mentoring programs and adequate practical facilities, is necessary to ensure the formed intention develops into a solid motivation for action.